2019
DOI: 10.3390/ma12081279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Scanning Speed on Microstructure and Properties of Laser Cladded Fe-Based Amorphous Coatings

Abstract: Fe-based amorphous alloys with excellent mechanical properties are suitable for preparing wear resistant coatings by laser cladding. In this study, a novel Fe-based amorphous coating was prepared by laser cladding on 3Cr13 stainless steel substrates. The influence of scanning speeds on the microstructures and properties of the coatings was investigated. The microstructure compositions and phases were analyzed by scanning electron microscope, electron probe microanalyzer, and x-ray diffraction respectively. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…They successfully produced high-quality coatings characterized by high hardness and better corrosion resistance compared with the base metal of the substrate [33].Another interesting example of manufacturing a high performance Fe-based coating is the study conducted by Li et al [34], which was an investigation of the effect of carbon fibers addition to Fe-based coatings produced by laser cladding. They demonstrated a significant increase in the microhardness and wear resistance of the composite coatings containing also nano-size carbides [34].Hou et al investigated the influence of scanning speed during the laser cladding of Fe-based amorphous coatings on the microstructure and properties of coatings [35]. They demonstrated that the laser cladding process could be successfully applied for manufacturing high-quality amorphous coatings.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They successfully produced high-quality coatings characterized by high hardness and better corrosion resistance compared with the base metal of the substrate [33].Another interesting example of manufacturing a high performance Fe-based coating is the study conducted by Li et al [34], which was an investigation of the effect of carbon fibers addition to Fe-based coatings produced by laser cladding. They demonstrated a significant increase in the microhardness and wear resistance of the composite coatings containing also nano-size carbides [34].Hou et al investigated the influence of scanning speed during the laser cladding of Fe-based amorphous coatings on the microstructure and properties of coatings [35]. They demonstrated that the laser cladding process could be successfully applied for manufacturing high-quality amorphous coatings.…”
mentioning
confidence: 99%
“…They demonstrated that the laser cladding process could be successfully applied for manufacturing high-quality amorphous coatings. They also demonstrated that the low cost of Fe-based amorphous alloys is an advantage [35]. Zhang et al demonstrated that deep cryogenic treatment, applied after laser cladding Fe-based coatings, can significantly enhance the microhardness and wear resistance of such coatings [36].An original technique of laser surface melting of non-ferrous alloys in liquid nitrogen was elaborated and demonstrated by and Cui et al [40].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On account of the short-range ordered and long-range disordered structure, the absence of crystalline defects, the homogeneity of the chemical composition, and the presence of passivity promoters and dissolution blockers, Fe-based amorphous alloys exhibit high strength, high hardness, high elastic strain, and preeminent corrosion and wear resistance [7][8][9]. However, it is difficult to produce Fe-based amorphous alloys with large sizes because the formation of amorphous alloys needs a great cooling rate and strict preparation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, the laser cladding technique has received much attention in academic research and industrial applications because of its inherent merits, such as metallurgical bonding, low dilution ratio, small heat-affected zone, accurate process control, and high efficiency [1,2]. It is well-known that Fe-based laser cladding coatings have exhibited many advantages including its low cost, closing to the composition of the substrate and acceptable compatibility.…”
Section: Introductionmentioning
confidence: 99%